Metal hydrides for hydrogen storage at low charging pressures - Fernades, Vitor R. (2010)
LaNi5 alloys are been extensively study as hydrogen storage material due their easy activation and good kinetics. LaNi5 alloys, containing substitutional elements such as Al or Ce, allow adjustments of the equilibrium pressure and absorption kinetics of the metallic hydrides making them storage candidate materials susceptible to be used in fuel cells systems. In this work, the thermodynamic properties of LaNi5-yAly and LaNi5, La1-xCexNi5 alloys were evaluated using a purpose built Sievert-type apparatus.